Factors behind the changes in small towns along the Selangor Northern corridor resulting from spillover of the Klang-Langat Valley Metropolitan region: a confirmatory factor analysis approach (CFA) - Yazid Saleh (Tanjong Malim, 2019)
Factors behind the changes in small towns along the Selangor Northern corridor resulting from spillover of the Klang-Langat Valley Metropolitan region: a confirmatory factor analysis approach (CFA) by Yazid Saleh